Effect of CO2 Flow Rate and Carbonation Temperature in the Synthesis of Crystalline Precipitated Calcium Carbonate (PCC) from Limestone - Sri Wardhani; Fanny Prasetia; Mohammad Misbah Khunur; Danar Purwonugroho; Yuniar Ponco Prananto (Universitas Gadjah Mada, 2018)
The effect of CO2 flow rate and carbonation temperature were studied in the synthesis of PCC from limestone using carbonation method. The synthesis was started by dissolving CaO that was obtained from calcination of limestone into HNO3 6M. The solution was then added with ammonia solution and then streamed with CO2 until pH 8 with flow rates of 0.5; 1.0; 1.5; and 2.0 L/min. The optimum flow rate obtained from this stage was then applied in the carbonation process with temperatures of 50, 80, 100, 150, 200, and 250 °C. The results showed that low flow rate give reasonably high yield but the yields obtained in every flow rate used in this work has insignificant difference based on F-test. The optimum flow rate used for the synthesis of PCC in the next stage was 0.5 L/min with a yield of 62.95%. Different carbonation temperature influences the polymorphs and crystallinity of the synthesized PCC. The synthesized PCC was analyzed by FT-IT, powder-XRD, SEM-EDX, and PSA. FT-IR analysis showed stretching vibrations of C–O at 1419, 1479, and 1384 cm-1 which correspond to calcite, vaterite, and aragonite respectively. Powder-XRD and SEM-EDX confirms that at the carbonation temperature of 50 °C, calcite and vaterite were formed, while at the carbonation temperature of 80 °C, mixture of calcite-vaterite-aragonite were obtained. Higher carbonation temperature changes the vaterite and aragonite polymorphs into calcite, and the best crystallinity was obtained at 250 °C. PSA analysis showed that the particle diameter of the synthesized PCC was about 3.58 to 38.14 µm.